Heliangolides from Viguiera sylvatica - Tamayo Castillo, Giselle (1989)
The extract of the aerial parts of Viguiera sylvatica gave, in addition to known heliangolides, four new heliangolides related to 1-desoxyniveusin A and one to 11,13-dihydrofuroheliangolide as well as three guaianolides, two of them derived from arbiglovin and one from estafiatin. Furthermore, two unreported geranyl nerol derivatives were isolated. The structures were elucidated by high field NMR spectroscopy.